Why management and leadership education for internists? - Martins, H (2010)
Around the world, there is an increasing need for more efficiency in healthcare alongside cost containment. Internal medicine physicians are in a pivotal position in this regard. In many countries, they act as bridges between ambulatory/continuity of care systems and hospital-based intensive care and sophisticated therapies. Within the medical field, they often bridge gaps between many specialities increasingly required to provide modern medical care. These skills of managing complex environments, being sensitive to health economics and using large amounts of information, are not normally taught or developed in programmes of internal medicine. While some skills are natural and acquired through practice, other skills would benefit from insights from the fields of management. On the other hand, it seems critical to have internists playing a leading role in the future care of aging populations, and they are the most likely to understand the needs of these multi-pathology cases. On a practical level, internists face the daily challenges of engaging and leading as many people as possible to provide the best care; this requires very good leadership, negotiation, team-working and change-management skills, all of which can be vastly enhanced with specific education initiatives that are targeted and customised to physicians' needs. Management education for internists should be "spiral", starting from medical school and expanding to incorporate issues as the physician matures into new activities and responsibilities. In practical terms, current internists and residents of internal medicine can be brought into contact with such education by a combination of workshops as well as residential and online courses.